Hemoglobin Levels of Pregnancy Women Against The Weight Of A Born In The Abi Ummi DW Sarmadi Clinic Palembang 2020 - Ratna Dewi (Institute Of Computer Science (IOCS), 2020)
Hemoglobin (Hb) is a parameter that is widely used to determine the prevalence of anemia. The mother's hemoglobin (Hb) level greatly affects the weight of the baby to be born. Pregnant women who are anemic due to low hemoglobin in addition to endangering the mother's life also interfere with growth and development and endanger the life of the fetus. Data from the Word Health Organization (WHO), the prevalence of anemia in pregnant women worldwide is 41.8%. The aim was to determine the relationship between maternal hemoglobin levels during pregnancy and birth weight at the Abi Ummi DW Sarmadi clinic in Palembang in 2020. The analytical survey research method used a cross sectional approach. The research population was all mothers and babies born at the Abi Ummi DW Sarmadi Clinic in Palembang at the time of the study. The research sample was taken by purposive sampling, amounting to 37 respondents. The results of the univariate study showed that mothers during pregnancy had normal hemoglobin levels with higher normal birth weight, namely 18 people (75.0%) compared to LBW birth weight, namely 2 people (15.4%) while mothers during pregnancy had hemoglobin levels with severe anemia. LBW births were greater, namely 11 people (84.6%) compared to normal birth weight, namely 6 people (25.0%). The results of the Chi Square statistical test showed that P-Value = 0.002 <? (0.05) means that there is a significant relationship between maternal hemoglobin levels during pregnancy and birth weight at the Abi Ummi DW Sarmadi clinic in Palembang in 2020. Advice to midwives or health workers at the Abi Ummi clinic Dw Sarmadi Palembang can improve education about anemia, check hemoglobin levels in the early and late trimesters of pregnancy during pregnancy visits so that one of the causes of anemia in pregnancy can be prevented as one of the causes of the occurrence of babies born with LBW. Keywords: Maternal Hemoglobin Levels During Pregnancy, Birth Weight